Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/epi.13577
|View full text |Cite
|
Sign up to set email alerts
|

Acute treatment with minocycline, but not valproic acid, improves long‐term behavioral outcomes in the Theiler's virus model of temporal lobe epilepsy

Abstract: Summary Objective Infection with Theiler’s murine encephalomyelitis virus (TMEV) in C57Bl/6J mice induces acute seizures and development of spontaneous recurrent seizures and behavioral comorbidities weeks later. The present studies sought to determine whether acute therapeutic intervention with an anti-inflammatory–based approach could prevent or modify development of TMEV-induced long-term behavioral comorbidities. Valproic acid (VPA), in addition to its prototypical anticonvulsant properties, inhibits hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 40 publications
(122 reference statements)
1
83
0
Order By: Relevance
“…However, 41% of TMEV‐infected C57BL/6J mice exhibited seizures within 6 days versus 74% of infected Ido1‐KO mice (Figure A). Examination of cumulative seizure burden has been efficacious in evaluating seizure severity and number over time . We found that cumulative seizure burden was greater in Ido1‐KO mice compared to C57BL/6J mice at day 6 p.i.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, 41% of TMEV‐infected C57BL/6J mice exhibited seizures within 6 days versus 74% of infected Ido1‐KO mice (Figure A). Examination of cumulative seizure burden has been efficacious in evaluating seizure severity and number over time . We found that cumulative seizure burden was greater in Ido1‐KO mice compared to C57BL/6J mice at day 6 p.i.…”
Section: Resultsmentioning
confidence: 94%
“…Seizure incidence was calculated by dividing the number of mice with seizures, ≥3 at any time during the study, by the number of mice infected in that genotype . Cumulative seizure burden for a particular day was calculated by adding the Racine score of that day to the sum of all preceding scores; any day without an observed seizure (Racine = 0) maintained the previous day's cumulative burden score …”
Section: Methodsmentioning
confidence: 99%
“…MIN possess acute anticonvulsant efficacy in the mouse 6 Hz model (median effective dose of 170 mg/kg, ip) . We chose to forgo any dose‐response with MIN because kindled rodents are more sensitive than naïve rodents to adverse drug effects and we have also previously reported mortality associated with MIN in mice with a history of seizures . Pilot studies with LTG‐resistant CKM resulted in mortality with MIN doses >100 mg/kg (data not shown), a dose well below that which is motor‐impairing in naive mice (250 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…A cohort of CKM from both treatment groups (n = 20/group), and sham‐kindled mice (n = 5), underwent behavioral assessment of general hyperexcitability during the kindling acquisition process and immediately after achieving kindling criterion based on a hyperexcitability test adapted from a rat post‐pilocarpine model . The mice were also tested shortly after the final kindling stimulation (day 21) in an automated open‐field (OF) test of anxiety‐like behavior …”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the Theiler's murine encephalomyelitis virus (TMEV) mouse model has emerged as a novel “hit and run” model that begins to address this matter . C57BL/6 mice, but not SJL mice, exposed to TMEV intracerebrally display many of the characteristics of encephalitis‐induced human temporal lobe epilepsy (TLE), including neuroinflammation, neurodegeneration, and behavioral comorbidities such as anxiety‐like behavior and cognitive deficit . Moreover, mice infected with TMEV that present with acute symptomatic seizures display reduced seizure threshold and an increased liability for the development of abnormal EEG activity and SRS for weeks to months following intracerebral inoculation with TMEV .…”
Section: Epileptogenesis In a Murine Model Of Viral Encephalitismentioning
confidence: 99%